Fractionated SRT using VMAT and Gamma Knife for brain metastases and gliomas — a planning study. (8th November 2015) - Huss, Marie; Barsoum, Pierre; Dodoo, Ernest; Sinclair, Georges; Toma‐Dasu, Iuliana
Abstract : Stereotactic radiosurgery using Gamma Knife (GK) or linear accelerators has been used for decades to treat brain tumors in one fraction. A new positioning system, Extend™, was introduced by Elekta AB for fractionated stereotactic radiotherapy (SRT) with GK. Another option for fractionated SRT is advanced planning and delivery using linacs and volumetric modulated arc therapy (VMAT). This project aims to assess the performance of GK Extend™ for delivering fractionated SRT by comparing GK treatments plans for brain targets performed using Leksell GammaPlan (LGP) with VMAT treatment plans. Several targets were considered for the planning: simulated metastasis‐ and glioma‐like targets surrounding an organ at risk (OAR), as well as three clinical cases of metastases. Physical parameters such as conformity, gradient index, dose to OARs, and brain volume receiving doses above the threshold associated with risk of damaging healthy tissue, were determined and compared for the treatment plans. The results showed that GK produced better dose distributions for target volumes below 15 cm 3, while VMAT results in better dose conformity to the target and lower doses to the OARs in case of fractionated treatments for large or irregular volumes. The volume receiving doses above a threshold associated with increased risk of damage to normal brain tissue was also smaller for VMAT. The GK consistently performed better than VMAT in producing a lower dose‐bath to the brain. The above is subjected only to margin‐dependent fractionated radiotherapy (CTV/PTV). The results of this study could lead to clinically significant decisions regarding the choice of the radiotherapy technique for brain targets. PACS numbers: 87.53.Ly, 87.55.D‐